Pengaruh Green Marketing Mix Terhadap Purchase Decision Dalam Menggunakan Eco Friendly Product - Husnatul Jennah; Andy Ismail (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
One of the causes of natural disasters is environmental damage, and many Indonesian communities are indifferent to their surroundings. This has prompted humans to develop technology that enables the production of environmentally friendly products. Consequently, companies have begun to employ new environmentally friendly marketing strategies, known as green marketing mix, which encompass environmentally friendly products, pricing, placement, and promotion. The objective of this research is to provide valuable insights for companies in developing their marketing strategies. This study involved eighty individuals from the community who are users of environmentally friendly products. The research falls under the category of quantitative research. The data used were primary data obtained through questionnaires distributed by the researchers. This research utilized path analysis with Partial Least Squares (PLS) as the analytical method. The results indicate that green products directly influence purchasing decisions, green pricing directly influences purchasing decisions, and green promotion directly influences purchasing decisions